Design and Implementation of Reconfigurable Virtual Instruments with User Defined Functionality - Jeevitha L; Sangeetha S; Arun pandiyan S (International Journal of Computer Sciences and Engineering, 2014)
Reconfigure multiple instruments in single hardware platform. In this project a low cost arbitrary waveform generator, Function generator, Digital Oscilloscope is proposed with low end microcontroller ï¿½ ARM LPC2148 which would generate a waveform of any shape and type required for functionality defined by user. The embedded hardware regenerates the user defined waveform with appropriate magnitude and frequency. The hardware is implemented with SDRAM support to make it portable, so that the user can download the standard and Non-standard type of waveform into the target hardware and generate the output waveform in oscilloscope. A high-level software application runs on the PC and provides a user interface to the operator select a virtual instrument (e.g. digital oscilloscope, arbitrary waveform generator, function generatorï¿½) from a library of instruments and configures the RVI system to convert it into the selected instrument with its associated console.